2022
DOI: 10.2147/amep.s359703
|View full text |Cite
|
Sign up to set email alerts
|

Attitude and Perception of Medical Students Towards Histology Subject at Wollo University, Ethiopia

Abstract: Introduction Students’ perceptions and feedback have a significant impact on academic progress. Objective To assess the attitude and perception of medical students towards histology subject at Wollo University, Northern Ethiopia. Methods An institution-based cross-sectional study design was carried out in Wollo University from January, 2021 to February, 2021. A pre-tested and structured self-administered questionnaire was used for data collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…This finding was in agreement with studies conducted in Ethiopia, Malaysia and South Asia, which revealed that there are few opportunities in basic medical science, which are limited to teaching, research, and diagnostic laboratories. 15 , 20 , 21 The current study also showed that nearly two third of medical students perceived that integrated curriculum with other basic sciences increased their interest in ward embryology course. This finding was higher than a reported study by Teshome et al which revealed only one third of medical students perceived that integrated curriculum with other basic sciences increased their interest in ward histology course.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…This finding was in agreement with studies conducted in Ethiopia, Malaysia and South Asia, which revealed that there are few opportunities in basic medical science, which are limited to teaching, research, and diagnostic laboratories. 15 , 20 , 21 The current study also showed that nearly two third of medical students perceived that integrated curriculum with other basic sciences increased their interest in ward embryology course. This finding was higher than a reported study by Teshome et al which revealed only one third of medical students perceived that integrated curriculum with other basic sciences increased their interest in ward histology course.…”
Section: Discussionsupporting
confidence: 56%
“…This finding was higher than a reported study by Teshome et al which revealed only one third of medical students perceived that integrated curriculum with other basic sciences increased their interest in ward histology course. 15 This discrepancy might be due to the difference between the two courses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We read with great interest the article by Teshome 1 which provides a unique insight into the perceptions and attitudes of medical students towards histology. We appreciate the authors’ efforts and would like to offer our comments.…”
Section: Dear Editormentioning
confidence: 99%